Rozwijanie kompetencji komunikacyjnej u ucznia z zespołem Aspergera - Róg, Tomasz (Neofilolog, 2011)
The paper reports the findings of a study that the author conducted in order to investigate the possibility of developing communicative compe-tence in a learner with Asperger‟s Syndrome. Information about the dis-order is followed by enquiry into the notion of the theory of mind which is said to determine the ability to communicate effectively. Since patients with Asperger‟s Syndrome do not demonstrate theory of mind, it is be-lieved they are unable to develop communicative competence. However, the literature in the field points to the therapeutic aspects of foreign lan-guage teaching and therefore the author explored the possibility of im-proving communicative skills in the case of a 13-year-old boy diagnosed with Asperger‟s Syndrome.